Serological and Molecular Survey of Babesia ovis in Healthy Sheep in Turkiye - Bozan, Mehmet; Ulucesme, Mehmet Can; Eyvaz, Arda; Ceylan, Onur; Sevinc, Ferda; Aktas, Munir; Ozubek, Sezayi (Mdpi, 2024)
Babesiosis, caused by Babesia ovis, is a major seasonal issue in sheep, particularly in countries like T & uuml;rkiye with high Rhipicephalus bursa tick populations. Previous studies employing various methods such as microscopy, serology, or molecular techniques have reported different epidemiological data concerning ovine babesiosis. Addressing this knowledge gap, our study employed a combined nested PCR (nPCR)/indirect ELISA (iELISA) approach, analyzing blood samples collected from 414 sheep between April and July 2023 using both techniques. nPCR amplified the 18S ribosomal RNA gene of B. ovis and determined a molecular prevalence of 1.9%. Conversely, serological testing using iELISA targeted the BoSA1 antigen and revealed a significantly higher positivity rate of 59.9% for anti-B. ovis antibodies. The temporary presence of Babesia after recovery reduces nPCR sensitivity, resulting in lower molecular prevalence. However, even if Babesia is not present in the host, anti-B. ovis antibodies remain in the serum for a long time and can be detected serologically. Our study underscores the necessity of concurrently employing molecular and serological methods for an accurate assessment of B. ovis prevalence. It highlights the importance of comprehensive epidemiological approaches for effective disease management in sheep populations.
Keywords: Babesia ovis; ELISA; epidemiology; PCR; sheep